THE INFLUENCE OF WORK DISCIPLINE, WORK MOTIVATION, AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE - Putri Hana Salsafila; Bintang Narpati; Murti Wijayanti; Tri Yulaeli (ZILLZELL MEDIA PRIMA, 2023)
This study aims to measure the Effect of Work Discipline, Work Motivation, and Work Environment on Employee Performance. The research method uses quantitative methods, where the objects used are employees at PT RJI. The number of samples used in this study was 100 respondents using non-probability sampling techniques (saturated sampling) and the data was processed using the SPSS program version 25 for windows. This study used primary data conducted by distributing questionnaires to PT RJI employees. Based on the results of the analysis conducted, it can be concluded that the variables of work discipline, work motivation, and work environment have a positive and significant effect on employee performance at PT RJI